Immigration attitudes amongst European Muslims: social identity, economic threat and familiar experiences. Issue 7 (19th May 2019) - Mustafa, Asma; Richards, Lindsay
ABSTRACT: Studies of immigration attitudes have typically taken the majority perspective, focusing on views of majority rather than minority groups. However, as modern societies have grown in diversity and more people within society have migration histories, this approach has become more partial. This article uses European Social Survey Round 7 to explore attitudes towards immigration from the perspective of Muslim Europeans. Muslim attitudes are compared to Christian and secular majority populations in eight European countries with large/moderate Muslim populations. We show that income has a weaker effect on Muslim attitudes compared to the secular majority and that Muslims hold more favourable attitudes towards migrants from poorer countries. We argue that European Muslim attitudes towards immigration fit better with Social Identity Theory and are less a consequence of competition. We propose an additional model for understanding immigration attitudes, whereby people's personal histories and experiences create empathy with others across national borders.